2015
DOI: 10.2215/cjn.04360514
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective International Multicenter Study of AKI in the Intensive Care Unit

Abstract: Background and objectives AKI is frequent and is associated with poor outcomes. There is limited information on the epidemiology of AKI worldwide. This study compared patients with AKI in emerging and developed countries to determine the association of clinical factors and processes of care with outcomes.Design, setting, participants, & measurements This prospective observational study was conducted among intensive care unit patients from nine centers in developed countries and five centers in emerging countri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
166
1
8

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 226 publications
(195 citation statements)
references
References 52 publications
13
166
1
8
Order By: Relevance
“…The results showed that the mortality risks increased with the increase of the APACHE II or SOFA score. Similarly, two international multicenter prospective studies separated by 10 years confirmed a similar effect of the APACHE II score for predicting mortality risk [24, 25]. These results indicate that APACHE II and SOFA scores can accurately predict critical illness and mortality risk in AKI patients.…”
Section: Discussionsupporting
confidence: 53%
“…The results showed that the mortality risks increased with the increase of the APACHE II or SOFA score. Similarly, two international multicenter prospective studies separated by 10 years confirmed a similar effect of the APACHE II score for predicting mortality risk [24, 25]. These results indicate that APACHE II and SOFA scores can accurately predict critical illness and mortality risk in AKI patients.…”
Section: Discussionsupporting
confidence: 53%
“…Although the pathophysiologic mechanism remains incompletely understood, it seems evident that the deleterious inflammatory cascade characteristic of sepsis contributes to the AKI as well 30. Patients with sepsis complicated by AKI have a significantly increased mortality relative to patients without AKI 263132. Furthermore, patients with AKI associated with sepsis have a significantly increased mortality relative to those with AKI of another etiology 31…”
Section: Definitionsmentioning
confidence: 99%
“…In high-income countries, patients are older and have more comorbidities, such as diabetes mellitus, cardiovascular disease, malignancy, and possibly chronic kidney disease (CKD) [1,16]. The most common causes for AKI in high-income countries are sepsis, hypovolemia, drugs, and ischemia [1,16,17], and AKI is often associated with other acute organ failures [16,17]. …”
Section: Causes and Patterns Of Aki In Western Countriesmentioning
confidence: 99%
“…Other causes of AKI, such as glomerulonephritis and acute interstitial nephritis, are more often diagnosed in intensive care units in LMICs than in high-income countries [16]. However, it is unclear whether these represent real differences or whether they reflect variations in practice patterns regarding kidney biopsies.…”
Section: Causes and Patterns Of Aki In Western Countriesmentioning
confidence: 99%
See 1 more Smart Citation